Homogeneous Derivatization of Sugarcane Bagasse with Myristyl Chloride at Room Temperature to Prepare Bio-based Oil Absorbents - Aiping Zhang; Chuanfu Liu; Jun Xie; Runcang Sun (BioResources, 2014)
Homogeneous myristoylation of sugarcane bagasse (SCB) was investigated at room temperature in dimethyl sulfoxide/N-methylimidazole (DMSO/NMI) without any additional catalysts. The effects of reaction time and the dosage of myristyl chloride on the extent of myristoylation were studied. The weight percent gain (WPG) of the modified SCB was 10.7 to 133.2%. The role of NMI as solvent, base, and catalyst at room temperature was proposed. FT-IR and solid-state CP/MAS 13C-NMR analyses provided evidence of myristoylation. The reactions of carbohydrate and lignin fractions were both confirmed. Solid-state CP/MAS 13C-NMR also implied the reaction of three hydroxyl groups at C-2, C-3, and C-6 positions in cellulose. The modified SCB could easily absorb oil with the capacity of 1.57 to 3.76 g/g for engine oil and 1.72 to 3.55 g/g for vacuum pump oil. The enhanced oil capacities exhibited similar trends in terms of WPG with increased reaction parameters. This modified SCB can be used as a potential oil absorbent.